Politics of Crisis: Threatening and Defending Journalistic Expertise—A Processual Account - Antony, Alexander; Steets, Silke; Pfadenhauer, Michaela (Symbolic Interaction, 2022)
In this article, we argue for making the frequently invoked notion of “crises of journalism” itself the proper subject of sociological analysis. Based on a case study of a public controversy over an adversarial TV interview with a well-known politician on Austria's public service broadcaster ORF, we provide an analysis of the practical use of crisis claims in metajournalistic discourse. Drawing on ethnomethodology, interactionism, and situational analysis and suggesting the discursive trajectory as an analytic tool, we show that crisis accounts serve as an instrument of politicizing journalistic expertise, i.e., as a discursive strategy of mobilizing heterogeneous actors to impose interpretations of how journalism ought to be.
CRIS-Team Scopus Importer:2022-06-03
Keywords: crisis claims; discursive trajectory; journalism; journalistic expertise; situational analysis